Identification of low-energy isovector octupole states in 144Nd. (June 2016) - Thürauf, M; Scheck, M; Bernards, C; Blanc, A; Cooper, N; Defrance, G; Jentschel, M; Jolie, J; Kaleja, O; Köster, U; Kröll, T; Mutti, P; et al.
Abstract: Recently, first candidates for low-lying isovector states in the octupole sector were suggested. The unambiguous identification of those states will contribute to the decomposition of the octupole-octupole residual interaction in an isoscalar and isovector part. This will help us understand the octupole degree of freedom. In 144 Nd the 3 − state at 2778 keV is a good candidate for such a "mixed-symmetry'' octupole state. In order to clarify the nature of this state, a 143 Nd(n, γ)-experiment was conducted with the EXILL-setup. Following neutron capture the 3 − states are populated and EXILL provides the opportunity to determine the multipole-mixing ratios of the 3i − →31 - transitions. For the transition from the "mixed-symmetry" octupole state to the symmetric 31 − state we expect a strong M 1 component.